Identification of Plant Extracts and Oils as Insect Repellents - Kumar, Eneyal Siva; Vieira, Maria; Doyle, Chloe (Biology, Engineering, Medicine and Science Reports)
Introduction: Plant-based insect repellents have been used for many years in traditional practice as a personal protection measure against insects. Development of new plant-based insect repel- lent is a valuable resource for environmentally safe crop production. In recent years, plant-based insect repellents have gained importance among farmers, as these are considered “Safe” to the environment as compared to synthetic pesticides. To date, several bio pesticides have been identified as insect repellent, however there is no single plant based product that gives complete repellency. This emphasis the need for identification of plant based bio pesticides with high re- pellency. Materials and Methods: The current study evaluated the potency of 11 plant extract of both Indian and Irish origin for their repellency against the grey field slug species. Extracts of Foeniculum vulgare (Fennel), Momordica charantia (Bitter Gourd), Trigonella foenum-graecum seeds (Fenugreek), Allium cepa (Shallots), Allium sativum (Garlic), Artocarpus heterophyllus (Jack Fruit) leaves, Phyllanthus emblica (Amla), Cymbopogon citrate (Lemon grass), Taraxacum officinale (Dandelion), Murraya koenigii (Curry leaves) and Curcuma longa (Turmeric) were used in this experiment. Plant extracts was prepared by crushing 5g of the sample in 100ml of water using pestle and mortar. The extracts as filtered using household sieve to remove larger particles and used to test their potency against the slugs. Results: Out of 11 extracts tested, five extracts repelled the slugs to a greater extent and three extracts showed moderate effect. However, three extracts had no effect. Conclusion: The results of this current study strongly suggest the use of five plant extracts such as garlic, fenugreek, fennel, bitter gourd and shallots as an envi- ronmentally safe bio pesticide to control grey field slugs.
Keywords: Natural product; Slugs; Repellents; Insects; Plant extracts; Home remedies